Effect of variables of sociodemographic on disease management skills on individuals with type 1 and type 2 diabetes receiving insulin therapy - Funda Sofulu; Elif Ünsal Avdal; Gökşen Polat; Gönül Düzgün (SERNEV, 2024)
Introduction: Self-care and self-management skills are at the forefront of disease management skills in individuals with Type 1 and Type 2 diabetes. An individual with diabetes who defines his/her self-care well will have increased his/her disease management skills as well as self-management skills to the desired level. The aim of this study is to evaluate the self-management skills of individuals with Type 1 and Type 2 diabetes receiving insulin therapy according to their sociodemographic characteristics.Method: The research is a prospective analytical study. Within the scope of the study, 913 individuals with Type 1 and Type 2 diabetes who applied to the diabetes polyclinic of a university hospital in Izmir in a month were included. The researchers collected the data through face-to-face interviews into Diabetes Patient Diagnosis Form and Diabetes Self-Management Skill Form.Results: In study 99.8% of the patients received diabetes education at least once and 60.8% of the individuals had never experienced hypoglycemia. When the diabetes self-management skills and self-insulin making skills of individuals with diabetes are examined; A statistically significant difference was found between the diagnostic variable categories in the sub-dimensions of medical nutrition therapy, exercise and treatment management, awareness of chronic complications, and diabetic outpatient care behaviors. It was determined that there was a significant difference between the education styles of individuals with diabetes, the frequency of blood sugar control and the frequency of hypoglycemia, and the sub-dimensions of diabetes self-management skills and the ability to make insulin on their own (p lt;0.001).Conclusion: Diabetes education given to individuals with diabetes contributes to their development of self-management skills. Multiple factors can affect individuals' self-management skills. As the number of educations, type of education, treatment methods, and education level of individuals with diabetes increase, their self-management skills and self-insulin making skills increase. If type 1 and type 2 diabetes patients can be followed closely and their training needs, diversity and application methods can be corrected, disease management will improve. Complications that may develop due to insulin application errors can be prevented.